Unravelling Chlamydia trachomatis diversity in Amhara, Ethiopia: MLVA-ompA sequencing as a molecular typing tool for trachoma. - Anna J Harte; Ehsan Ghasemian; Harry Pickering; Joanna Houghton; Ambahun Chernet; Eshetu Sata; Gizachew Yismaw; Taye Zeru; Zerihun Tadesse; E Kelly Callahan; Scott D Nash; Martin J Holland (Public Library of Science (PLoS), 2024)
Trachoma is the leading infectious cause of blindness worldwide and is now largely confined to around 40 low- and middle-income countries. It is caused by Chlamydia trachomatis (Ct), a contagious intracellular bacterium. The World Health Organization recommends mass drug administration (MDA) with azithromycin for treatment and control of ocular Ct infections, alongside improving facial cleanliness and environmental conditions to reduce transmission. To understand the molecular epidemiology of trachoma, especially in the context of MDA and transmission dynamics, the identification of Ct genotypes could be useful. While many studies have used the Ct major outer membrane protein gene (ompA) for genotyping, it has limitations. Our study applies a typing system novel to trachoma, Multiple Loci Variable Number Tandem Repeat Analysis combined with ompA (MLVA-ompA). Ocular swabs were collected post-MDA from four trachoma-endemic zones in Ethiopia between 2011-2017. DNA from 300 children with high Ct polymerase chain reaction (PCR) loads was typed using MLVA-ompA, utilizing 3 variable number tandem repeat (VNTR) loci within the Ct genome. Results show that MLVA-ompA exhibited high discriminatory power (0.981) surpassing the recommended threshold for epidemiological studies. We identified 87 MLVA-ompA variants across 26 districts. No significant associations were found between variants and clinical signs or chlamydial load. Notably, overall Ct diversity significantly decreased after additional MDA rounds, with a higher proportion of serovar A post-MDA. Despite challenges in sequencing one VNTR locus (CT1299), MLVA-ompA demonstrated cost-effectiveness and efficiency relative to whole genome sequencing, providing valuable information for trachoma control programs on local epidemiology. The findings suggest the potential of MLVA-ompA as a reliable tool for typing ocular Ct and understanding transmission dynamics, aiding in the development of targeted interventions for trachoma control.